View of the Naugaza Shantinatha Temple - Temples of India Project Team (Jio Institute, 2024)
Seen here is the view from the north of the Naugaza Shantinatha Temple. All that remains of the temple is its plinth and the colossal Jina image enshrined in the temple, which can be seen from far away. The Naugaza Temple has a garbhagriha (sanctum sanctorum), mandapa (pillared hall) and mukhamandapa (front porch) in plan. The remains of the superstructure have not survived. The plinths with elephant and human figure friezes demarcate the original plan of the temple.